Estratégias de marketing educacional no ensino superior privado - Batista Junior, Paulo Roberto Carvalho (2009)
This paper investigates the influence of strategic planning, marketing and communications at university, (assuming the focus of customer-focused marketing) in the process of gaining admission to higher education in the area of Business Administration. It was started as Exploratory Study, supported by secondary data and case study in private institution, UNAMA, after listening to the same leadership, as a person with experience, developed a descriptive study with a sample of students newly entering Course Directors to identify factors that influenced in their decision-making process of selecting the IES and evaluate, among them, what was the real influence of marketing strategies and communication used by the organization. The research aimed to investigate the influence of strategic planning, marketing and communications at university, (assuming the focus of marketing focused on client), the process of winning candidates for tertiary education in Business Administration. We made some assumptions that guided the development of research. It is evident that with respect to the use of educational marketing strategies may interfere with the decision by a candidate for the IES to higher education, however, when we analyze how this factor only 11% of those interviewed said they were in fact influenced by advertisement IES. Realizing this way that the marketing strategies used in educational communication process in the IES study, are very effective when analyzed the means by which the candidate notes the exam, but the evidence is that it is the process of communicating the main factor that influences the choice of UNAMA. But in the case studied, UNAMA, the most influential factors related to the strategic issues of IES are the issues of brand / tradition and as the fact of being the only private university in the state of Para, were important for students this research. It was also an assumption of the study was to evaluate whether there is educational marketing strategies that can be identified as more relevant than others to be prioritized by educational administrators in planning their marketing IES. Research can be concluded that the promotional strategies were less effective than investment in brand image, steeped in the tradition of IES.